Transmission Quality Measurements in DAB+ Broadcast System - Gilski Przemysław; Stefański Jacek (Metrology and Measurement Systems, 2017)
In the age of digital media, delivering broadcast content to customers at an acceptable level of quality is one of the most challenging tasks. The most important factor is the efficient use of available resources, including bandwidth. An appropriate way of managing the digital multiplex is essential for both the economic and technical issues. In this paper we describe transmission quality measurements in the DAB+ broadcast system. We provide a methodology for analysing parameters and factors related with the efficiency and reliability of a digital radio link. We describe a laboratory stand that can be used for transmission quality assessment on a regional and national level.